Reflecting, Measuring, Projecting: MoCA in Long-Term Care Facilities (ELEAM) from Clinical Experience to Occupational Therapy Research - Espinosa Varas, Jaime Andrés (Relatos Journal, 2025)
Population aging in Chile has increased the prevalence of cognitive impairment in Long-Term Care Facilities for Older Adults (ELEAM), affecting more than 60% of residents and highlighting the need for sensitive and contextually adapted assessments. Traditional instruments, such as the Pfeiffer questionnaire or the Mini-Mental State Examination, show limitations in detecting mild impairments, which has encouraged the incorporation of the Montreal Cognitive Assessment (MoCA) as a more sensitive tool. This article systematizes the experience of applying the MoCA in three ELEAM facilities in the Valparaíso Region between 2022 and 2025, with approximately 60 residents assessed. The results demonstrate its usefulness in identifying deficits in delayed memory and executive functions, as well as limitations in cases of severe cognitive impairment and among individuals with low educational attainment. The integration of complementary instruments, such as the Functional Independence Measure (FIM), the Hernández-Neuman Index (AVDi), the Frontal Assessment Battery (FAB), and the Memory Alteration Test (T@M), enabled a more comprehensive analysis and the development of person-centered interdisciplinary care plans. This experience strengthened the role of the occupational therapist as a key link between cognitive assessment and functionality, while projecting the need for an exploratory descriptive-correlational study to validate and adapt the MoCA in the Chilean context, providing evidence to support its inclusion in institutional protocols and public policies for the care of institutionalized older adults.
Keywords: MoCA; Occupational Therapy; Cognitive Assessment; Long-Term Care Facilities; Experience Systematization